2018
DOI: 10.5301/ejo.5001074
|View full text |Cite
|
Sign up to set email alerts
|

Sequential tissue plasminogen activator, pneumatic displacement, and anti-VEGF treatment for submacular hemorrhage

Abstract: Sequential IV tPA, PD, and IV anti-VEGF treatments for SMH in patients with nAMD is effective. However, further studies are needed to establish the best treatment algorithm for SMH in patients with nAMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
(52 reference statements)
1
4
0
1
Order By: Relevance
“…A beneficial effect of improved visual outcome following post-operative anti-VEGF injection was shown by Chang et al 9 at 6 months in their series compared to the group of eyes that did not receive post-operative anti-VEGF. Our final average BCVA (1.07) result is comparable to the most recent study by Bardak et al 12 and Bell et al 11 Better visual results were observed by De Silva and Bindra 15 in a smaller study.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…A beneficial effect of improved visual outcome following post-operative anti-VEGF injection was shown by Chang et al 9 at 6 months in their series compared to the group of eyes that did not receive post-operative anti-VEGF. Our final average BCVA (1.07) result is comparable to the most recent study by Bardak et al 12 and Bell et al 11 Better visual results were observed by De Silva and Bindra 15 in a smaller study.…”
Section: Discussionsupporting
confidence: 89%
“…Most series use pneumatic displacement with expansible gas + intravitreal tPA ± anti-VEGF injections or PPV with subretinal tPA. 8,9,11,12,15 All our patients received PPV with either subretinal tPA or intravitreal tPA depending on surgeon preference. We did not observe any differences with either subretinal/intravitreal tPA though the numbers in each arm were small.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,9,16 On the contrary, recent publications exploring intravitreal injection of tPA and gas showed relatively favorable outcomes even in these difficult cases. 18,19 Hassan et al 5 Figure 1. A 74 year old female who presented with a relatively small sub-macular hemorrhage (SMH) in her left eye, visual acuity was 20/40.…”
Section: Discussionmentioning
confidence: 99%
“…[62] SMH tedavisinde subretinal fibrini parçalayan plazmin molekülünün aktivasyonunu sağlayan intravitreal veya subretinal tPA enjeksiyonları, SMH'yı foveal alandan perifere itmek amacıyla intravitreal gaz veya hava enjeksiyonları ve anti vasküler endotelyal büyüme faktörü (anti-VEGF) enjeksiyonları veya bunların kombinasyonları şeklindedir. [63][64][65] Sonuçta hangi tedavi uygulanırsa uygulansın erken tanı ve erken yapılacak bir müdahale ile oldukça iyi sonuçlar alınabileceği gibi geç kalınmış vakalarda ve geniş kanamalarda fotoreseptör hücre hasarı ve skar gelişimine bağlı olarak iyi bir görsel sonuç almak mümkün olmayabilir.…”
Section: Travmatik Submakuler Hemoraji (Smh)unclassified